Molluscum contagiosum could become an early sign of HIV infection - Hardiani, Ni Luh Raka M.; Suryana, Ketut; Suhardinatha, Kadek A. (International Journal of Advances in Medicine, 2022)
HIV is a type of virus that attack the immune system, causing it unable to function normally and putting the person in a condition called immunocompromised and is vulnerable to lots of infection. People living with HIV are prone to complications if there is persisting infection and inflammation. One of the inflammation markers is the neutrophil-lymphocyte ratio (NLR). Complication on the skin is one of the frequently happened. One of it is Molluscum contagiosum. Molluscum contagiosum caused by virus infection which target the epidermal layer of the skin that result in formation of round, umbilicated, painless papule or nodule. In this case report, we present a male, 49 years old which has complained of persistent fatigue and diarrhea. There is multiple rounds, skin-colored, painless papules on his face and neck since 6 month ago which keep increasing. Laboratory result show decrease in hemoglobin and high neutrophil lymphocyte ratio. In HIV, the NLR value has a significant negative correlation with the CD4 amount. The existence of molluscum contagiosum in an adult with unknown HIV status need to be considered as a possibility of an immunocompromised especially if accompanied with other conditions. In the patient with HIV, with the existence of Molluscum contagiosum, the possibility of decreasing CD4 and increasing viral load need to be suspected. The patient’s obedience in consuming ARV also needs a careful attention.